A novel biomarker for predicting sepsis mortality: SCUBE-1. Issue 6 (12th February 2021) - Erdoğan, Murat; Findikli, Hüseyin Avni; Okuducu Teran, İrem
Abstract : Abstract: The mortality rate of patients diagnosed with sepsis is high. To date, many markers in sepsis patients have been studied to diagnose, determine their prognosis, and contribute to treatment. These studies were conducted in both experimental and clinical settings, but clinical trials remain limited. Therefore, more well-planned clinical studies are needed in patients with sepsis. The current study aimed to examine the prognostic role of signal peptide-CUB-epidermal growth factor-like domain-containing protein 1 (SCUBE-1) in sepsis and sepsis-related mortality. We also wanted to study its relationship with inflammatory markers and scoring systems. This prospective, cross-sectional, observational study included a total of 187 sepsis cases treated in the intensive care unit. Venous samples were obtained after diagnosis. The patients were separated into 2 groups: (1) the survivor group who were discharged or transferred within 28 days of the first diagnosis and (2) the nonsurvivor group who died within 28 days of the first diagnosis. The SCUBE-1, C-reactive protein, procalcitonin, creatinine, lactate values, acute physiology and chronic health evaluation 2, sequential organ failure assessment scores were significantly higher in the survivor group, and platelets were higher in the survivor group. In addition, SCUBE-1 positively correlated with the inflammatory markers C-reactive protein, lactate, sequential organ failure assessment, and acute physiology and chronic health evaluation 2. Additionally, the SCUBE-1 value predicts 28-day mortality, and the optimal cutoff value for predicting mortality is 4, 73 pg/mL. Sepsis is a disease with high mortality. SCUBE-1 can be used as a new prognostic factor for sepsis patients.